Frequency, Pattern and Rationale of Tooth Extractions Among Orthodontic Patients: A 10-year Tertiary Institution Experience - Elfleda Aikins; Chinyere Ututu (Khalij-Libya Journal of Dental and Medical Research, 2021)
Background and objectives: Tooth extractions are a vital aspect of orthodontic management that enables the orthodontist to achieve good aesthetics and function as well as long term treatment stability for the patient. Extractions may be necessary for various reasons among which are tooth size arch length discrepancy (TSALD), increased overjet and facial profile. The aim of this study was to determine the prevalence, pattern and rationale of tooth extraction among orthodontic patients attending the Orthodontic Unit of the Department of Child Dental Health, University of Port Harcourt Teaching Hospital. Methods. A retrospective study of a cohort of patients who attended one of the outpatient Orthodontic Clinics in the Department of Child Dental Health, University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria between 2011 and 2021. Data was collected from the patients’ records. Results. A total of 175 patients comprising 70(40%) males and 105(60%) females were included in the study. 67(38.3%) patients had at least one extraction. Twenty-eight (41.8%) extraction cases had extraction of the first premolars. Two-unit extractions of the maxillary first premolars (13, 46.4%) was the most frequent extraction pattern. Eight (29.6%) had extraction of primary canines only. Twenty-seven (40.3%) participants had extractions due to increased overjet. Over a third of the patients had extraction of at least one tooth. Conclusion. Two-unit extractions of maxillary first premolar was the commonest extraction pattern. Increased overjet was the commonest reason for extraction.